Functional and structural studies of lipase from Candida antarctica (CalB) treated in pressurized fluids - Feiten, Mirian Cristina (2018)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Engenharia de Alimentos, Florianópolis, 2018.